Effectiveness of stretching on reducing muscle and bone pain in worker - Siagian, Masryna; Butar-Butar, Emely Thania; Rizki, Kartika Sari; Artiani, Litri; Siregar, Ryskina Fatimah; Putri, Disti Amanda (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Musculoskeletal pain is a common work-related ailment in Indonesia. Although not fatal, it can significantly reduce worker productivity. Stretching exercises are often used to alleviate this pain. Pre-work stretching and warm-up exercises may reduce the risk of musculoskeletal pain and fatigue, improve muscle balance and posture, and promote muscle relaxation by lengthening tense muscles, thus increasing comfort during work. This study aimed to determine the effectiveness of stretching in reducing musculoskeletal pain among workers at the Opak Suli Factory in Sukaraya Bakti Village, Pancur Batu District, Deli Serdang Regency. The experimental study employed a pre-test and post-test control group design. All 38 workers at the Opak Suli Factory in Sukaraya Bakti Village, Pancur Batu District, Deli Serdang Regency, were included using total sampling and divided into an intervention group and a control group, each consisting of 19 workers. The intervention group showed a statistically significant reduction in musculoskeletal pain (p < 0.001), indicating that stretching was effective. In contrast, the control group showed no significant change (p = 0.083). In conclusion, stretching is an effective method for reducing musculoskeletal pain among the workers in this study.